2005
DOI: 10.1194/jlr.m400339-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

Downstream effects on human low density lipoprotein of homocysteine exported from endothelial cells in an in vitro system

Abstract: A model system is presented using human umbilical vein endothelial cells (HUVECs) to investigate the role of homocysteine (Hcy) in atherosclerosis. HUVECs are shown to export Hcy at a rate determined by the flux through the methionine/Hcy pathway. Additional methionine increases intracellular methionine, decreases intracellular folate, and increases Hcy export, whereas additional folate inhibits export. An inverse relationship exists between intracellular folate and Hcy export. Hcy export may be regulated by i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 53 publications
2
13
0
Order By: Relevance
“…This supports the idea of a ''field effect'' in people with enhanced risk of colorectal cancer (35). The observed inverse association between colon mucosal folate and plasma homocysteine reflects the importance of cellular folate metabolism to extracellular homocysteine concentrations (36), and confirms that modest folic acid supplements can elicit significant homocysteine-lowering (37). The study has revealed interactions between genotype and histology in determining response to folate and riboflavin supplementation.…”
Section: Discussionsupporting
confidence: 71%
“…This supports the idea of a ''field effect'' in people with enhanced risk of colorectal cancer (35). The observed inverse association between colon mucosal folate and plasma homocysteine reflects the importance of cellular folate metabolism to extracellular homocysteine concentrations (36), and confirms that modest folic acid supplements can elicit significant homocysteine-lowering (37). The study has revealed interactions between genotype and histology in determining response to folate and riboflavin supplementation.…”
Section: Discussionsupporting
confidence: 71%
“…3). In support of these findings, other investigators have demonstrated that Met-loaded endothelial cells exhibit increased accumulation and enhanced extracellular transport of Hcy metabolites, factors that are associated with an upregulation of inflammatory molecules, oxidative stress, and an increased susceptibility to coronary artery disease (35,43). Furthermore, studies of minipigs on a methionine-rich caseinate-based diet (42) and in patients with prevalent cardiovascular disease (50) show that Met intake correlates positively with hypertension.…”
Section: Discussionsupporting
confidence: 58%
“…homocysteine thiolactone. Homocysteine thiolactone forms homocysteine thiolactone-LDL-aggregates with the increased amount of LDL particles in chronic re-nal failure, which augments the phagocytotic activity of macrophages, and leads to an increased formation of foam cells in the atherosclerotic plaques [28]. The homocysteinylation of LDL particles increases their susceptibility to oxidation, induces the production of antihomocysteinyllysine antibodies, and accelerates their uptake to macrophages [29,30].…”
Section: Discussionmentioning
confidence: 99%